2020
DOI: 10.3892/or.2020.7715
|View full text |Cite
|
Sign up to set email alerts
|

miR‑3133 inhibits proliferation and angiogenesis by targeting the JUNB/VEGF pathway in human umbilical vein endothelial cells

Abstract: Membranous obstruction of the inferior vena cava (MOVC) has the highest incidence rate among the different types of Budd-Chiari syndrome (BCS) in China. The inferior vena cava septum of patients with MOVC contains capillaries and the two surfaces of the membrane are composed of vascular endothelial tissue. Membrane formation occurs due to endothelial damage. MicroRNAs (miRNAs/miRs) have been verified to be involved in the pathogenesis and progression of various human diseases. A previous study by our group sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Vascular endothelial growth factor can modulate the proliferation and angiogenesis of vascular endothelial cells and significantly correlate with thrombogenesis 32 . A study by Mengdie Xu's 5 team found that VEGF is a target for the regulation of HUVECs. The results from our study present the high secretion of VEGF from HUVECs when treated with overexpressing lncRNA MTUS2‐5 transfection or EVs from BCS patients, which is consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial growth factor can modulate the proliferation and angiogenesis of vascular endothelial cells and significantly correlate with thrombogenesis 32 . A study by Mengdie Xu's 5 team found that VEGF is a target for the regulation of HUVECs. The results from our study present the high secretion of VEGF from HUVECs when treated with overexpressing lncRNA MTUS2‐5 transfection or EVs from BCS patients, which is consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis with increased blood viscosity is considered to be the most common pathophysiological mechanism 4 . Aberrant expression of vascular endothelial growth factor (VEGF) and relative cytokines was reported in the serum of patients with membranous obstruction of the inferior vena cava (MOVC), which is the main type of BCS in China 5,6 . Therefore, the formation of the inferior vena cava diaphragm probably starts from proliferation and angiogenesis of vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a TF, JunB is implicated in the regulation of the VEGF signaling pathway, the differentiation of Th2 and Th17 cells, and the expression of human papillomavirus e6 and e7 oncoproteins ( Rengarajan et al., 2002 ; Henderson et al., 2004 ; Schmidt et al., 2007 ; He and Luo, 2012 ; Carr et al., 2017 ; Hasan et al., 2017 ; Yoshitomi et al., 2017 ; Xu et al., 2020 ). It has been reported that individual or multiple TFs form intracellular mono- or multi-element condensates to regulate the corresponding transcriptional activities ( Smith et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…JUNB is an ER-dependent gene found only in premenopausal women. [ 38 , 39 ] The JUNB gene has been shown to play an important role in the advancement of hepatocellular carcinoma and lung cancer and it is strongly associated with patient survival, suggesting a novel function of JUNB in cell proliferation and tumor aggressiveness. [ 40 , 41 ] We discovered little convincing evidence for the JUNB gene in our search of the literature, and therefore, the bioinformatics analysis performed in this study increases our understanding of this gene.…”
Section: Discussionmentioning
confidence: 99%